2010
DOI: 10.1007/s12011-010-8936-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Boron Differentially Alters Expression of Borate Transporter (NaBCl) mRNA by Jejunum and Kidney of Growing Pigs

Abstract: Inorganic boron (B), in the form of various borates, is readily absorbed across gastrointestinal epithelia. Although there is no stated B requirement, dietary B supplementation is thought to positively affect animal growth and metabolism, including promotion of bone strength and cell proliferation. Because of effective homeostatic control of plasma B levels, primarly by renal excretion, B toxicity in animals and humans is rare. The mechanisms responsible for improved animal performance and borate homeostasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Although there is some evidence for the tissue ubiquity of NaBC1 38 , we confirmed its presence in our cellular system under the same experimental conditions (after 3 or 15 days of culture and under basal or differentiation media) used in subsequent differentiation studies. When MSCs NaBC1 mRNA were amplified by qPCR, the results showed that in all the conditions assessed, NaBC1 gene expression was upregulated exclusively by borax and that this upregulation was dose-dependent (Supplementary Fig.…”
Section: Resultssupporting
confidence: 75%
“…Although there is some evidence for the tissue ubiquity of NaBC1 38 , we confirmed its presence in our cellular system under the same experimental conditions (after 3 or 15 days of culture and under basal or differentiation media) used in subsequent differentiation studies. When MSCs NaBC1 mRNA were amplified by qPCR, the results showed that in all the conditions assessed, NaBC1 gene expression was upregulated exclusively by borax and that this upregulation was dose-dependent (Supplementary Fig.…”
Section: Resultssupporting
confidence: 75%
“…Although there is some evidence for the tissue ubiquity of NaBC1 [47] , we confirmed its presence in our cellular system under the same experimental conditions (after 3 or 15 days of culture and under basal or differentiation media) used in previous studies. When MSCs NaBC1 mRNA were amplified by qPCR, the results showed that in all the conditions assessed, NaBC1 gene expression was upregulated exclusively by boron and that this upregulation was dose-dependent ( Figure S6-a).…”
Section: Boron Up-regulates Nabc1 and Fn-binding Integrins Expressionsupporting
confidence: 84%
“…We also investigated the gene expression of the late expressed markers involved in osteogenic (osteopontin-OPN) and adipogenic (Lipoprotein lipase-LPL) [47] differentiation by qPCR after 15 days of culture. These results demonstrate that the simultaneous stimulation of NaBC1 and FN-binding integrins promotes osteogenesis (in basal conditions) and strongly inhibits adipogenesis, even in an adipogenic induction medium.…”
Section: Figure S5-b Shows the Qpcr Analysis Of Specific Gene Encodinmentioning
confidence: 99%
“…In the same study of pigs as was mentioned above, a doubling of dietary boron content, maintained over 18 days, resulted in a twofold decrease (rather than the increase observed in the jejunum) in renal BTR1 transcript abundance (583). A quadrupling of normal dietary boron intake had no greater effect on renal BTR1 transcript abundance (583). The consequence of the downregulation is not known, but is consistent with a role of renal BTR1 in boron homeostasis.…”
Section: Causes Of Btr1 Downregulationmentioning
confidence: 55%
“…I) Increased transcript abundance following dietary boron supplementation. In a study of pigs, a doubling of dietary boron content, maintained over 18 days, resulted in a threefold increase in BTR1 transcript abundance in jejunal preparations but no increase in ileal preparations (583). A quadrupling of normal dietary boron intake had no greater effect on BTR1 transcript abundance in either the ileum or jejunum (583).…”
Section: Causes Of Btr1 Upregulationmentioning
confidence: 98%